Reduced interfacial recombination in perovskite solar cells by structural engineering simulation. (1st November 2022) - Prasanna, J Lakshmi; Goel, Ekta; Kumar, Amarjit; Kumar, Atul
Abstract: This theoretical study performed configurational optimization of heterojunction perovskite solar cells to minimize internal recombination through simulation. Interfacial recombination at the absorber-electron transport layer (ETL) junction is one of the prime sources of recombination in perovskite solar cell devices. Carrier density control in the vicinity of interfaces across absorber/ETL junction lowers the interfacial recombination. We explore various design alterations to achieve this condition, such as (a) restricting the majority carrier at the interface or asymmetric doping at perovskite/ETL interfaces, (b) widening the absorber bandgap at the interface, (c) donor interfacial defect at perovskite/ETL junction, (d) high rear doping of hole transport layer at back contact. We investigated the feasibility of these structural optimizations for lowering the overall internal recombination through the device. We achieved an optimized device by incorporating all these methods, which have improved efficiency, fill factor, and V OC by 38.61%, 5.5% and 21.69%, respectively, over the benchmark device. The optimized perovskite structure may provide valuable guidelines to experimentalists for achieving the high efficiency of the perovskite solar cells.